Dinamika Perilaku Takut pada Anak Usia Dini - Raden Rachmy Diana; Indah Maysela Azzahra (SALIHA: Jurnal Pendidikan & Agama Islam, 2021)
Fear behavior must exist in every human being. This behavior begins to appear in a person since he was born into the world, namely starting in early childhood. The dynamics of fearful behavior in children must occur, as parents and other adults should be able to respond to this problem well. Society in general understands that girls have a higher level of fear than boys. This study was conducted to determine the behavior of fear in boys and girls, and to find out how to respond to fearful behavior in early childhood. The research method used is descriptive qualitative, which describes the dynamics of fearful behavior in early childhood and how to respond to it. Data collection techniques in the form of observation sheets, interview sheets, and documentation. This research was conducted in the Sebiduk Sehaluan Ananda Playgroup (KB) which is located in the village of Sukanegeri, West Semendawai District, East OKU Regency, South Sumatra Province. The research subjects were early childhood children in Sebiduk Sehaluan Ananda Family Planning, which amounted to 19 children, and their parents. The results of the study based on observation sheets and interview sheets with parents that boys and girls have fearful behavior. In boys, the most common fears are the fear of the dark, the fear of lightning and the fear of ghosts. While girls are more afraid of animals, the dark, lightning and ghosts. But there are also boys and girls who are afraid of other things. The parenting methods for parents in responding to the dynamics of fearful behavior in early childhood are: 1) Providing supervision of children's activities; 2) Motivating children with positive words and behavior; 3) Provide an explanation regarding the child's fear and the object being feared; 4) Increase children's self-confidence; 5) Provide facilitation and provide solutions; 6) Calm the child with affection; 7) Do not frighten children with various things and events; 8) Provide advice; 9) Be a role model for children, because children are great imitators and easily absorb everything they see; 10) Giving treatment, making children aware that their behavior is wrong and committed to maintaining the chosen behavior; 11) Grow and increase children's piety and faith in God Almighty to always ask for protection only from Allah SWT, the ruler of the world and everything it.